Integrated Analysis of lncRNA and mRNA in Subcutaneous Adipose Tissue of Ningxiang Pig - Yan Gong; Jun He; Biao Li; Yu Xiao; Qinghua Zeng; Kang Xu; Yehui Duan; Jianhua He; Haiming Ma (Biology, 2021)
Ningxiang pigs, a Chinese bred pig known for its tender meat and high quality unsaturated fatty acids. This study discovers the transcription profiles and functional networks in long non-coding RNA (lncRNA) and messenger RNA (mRNA) in subcutaneous adipose tissue. Subcutaneous adipose tissue was collected from piglet, nursery pig, early fattening, and late fattening stage of Ningxiang piglets, and lncRNA and mRNA transcription of each stage was profiled. A total of 339,204,926 (piglet), 315,609,246 (nursery), 266,798,202 (early fattening), and 343,740,308 (late fattening) clean reads were generated, and 2872 novel lncRNAs were identified. Additionally, 10,084 differential mRNAs (DEmRNAs) and 931 differential lncRNAs were determined. Most DEmRNAs were up-regulated in the piglet stage, while they were down-regulated in late fattening stage. A complicated interaction between mRNAs and lncRNAs was identified via STEM and WGCNA, demonstrated that lncRNAs are a significant regulatory component in mRNAs. The findings showed that modules 2 and 5 have a similar mode of transcription for both mRNA and lncRNA, and were mainly participated in steroid biosynthesis, glycosphingolipid biosynthesis, metabolic pathways, and glycerolipid metabolism. The mRNAs and lncRNAs transcription levels of both modules was higher in the early and late fattening stage, which may be due to the active activity of the metabolism in relation to fatty acids, sterols, steroids, and lipids in the subcutaneous adipose tissue during the early and late fattening stage. These findings could be expected to result in further research of the functional properties of lncRNA from subcutaneous adipose tissue at different stages of development in Ningxiang pigs.